Mandatory Forensic Expertise of Audio-Video Recordings When they are Disputed in a Criminal Case - Gradinaru, Sandra (Acta Universitatis Danubius. Juridica, 2024)
In the context of technological advancement and the increasing use of audio and audio-video recordings as evidence in criminal proceedings, in order to ensure the right to a fair and the defendant’s right to defend itself, it is necessary to perform an a posteriori check of such evidence in the situation where its authenticity is disputed. A posteriori control of tapings used as evidence in criminal trials can be achieved only by an expert, which represents a legal means of evidence of great importance and consists in the conduct of investigations, analyses, assessments and conclusions of a technical nature. In case-law we note that the forensic technical expertise on digital data is rarely issued by courts. We also note that the reasoning of the courts in approving or denying such evidence is insufficient and unclear. To justify the denial of the evidence consisting in forensic technical expertise, the courts invoked reasons such as the celerity of criminal trials, the lack of usefulness of such proof (without providing a detailed analysis), and the court’s own judgement regarding the authenticity of the recordings, from simply viewing / listening to the tapes. We believe that the courts should actively investigate the authenticity of the records used as evidence, since any deletion, editing, insertion of replicas or alteration of the original content of a recording can lead to a change in the meaning of a conversation. If an evidence is proved to be altered, it is necessary to eliminate such evidence from the case file.